Análisis de viabilidad para la integración de tecnologías Power to Gas a partir de hidrógeno, dentro de la operación de una microrred eléctrica para zonas rurales en Colombia (2020)
Power to Gas (PtG) is an emerging technology, in which water electrolysis produces hydrogen that combined with CO2 generates synthetic gas. This technology makes it possible to take advantage of renewable electric energy generated within a microgrid, by using the excess of generated power and using it to feed the plant that performs the water electrolysis process. It is also an alternative for energy storage, since both hydrogen and synthetic gas can be stored in tanks. It is also an alternative for energy storage, since both hydrogen and synthetic gas can be stored in tanks. Additionally, the production of hydrogen and synthetic gas can be used to supply vehicles, to feed thermoelectric generation, and to integrate hydrogen into natural gas networks. PtG is a technology that can be used to provide multiple services within a microgrid. Existing projects around this technology currently use hydrogen mainly to create fuels, chemicals, and synthetic gas [9]. Despite its potential, this technology still has high costs, and therefore there are not many projects in place, nor much detailed research on its implementation. In Latin America, Argentina is the only country with a PtG plant as far as research is concerned [10]. Most of the projects are in Europe, especially in Germany and Denmark. Their main applications are based on the production of fuel, chemicals for industry and to inject hydrogen directly into the natural gas network. Therefore, this project seeks to analyze how viable it is to integrate PtG technology into a microgrid in terms of costs, production, energy benefits, useful life, among others; in the context of the microgrids of the isolated regions in Colombia. The present work is conformed in the following way: initially a set of definitions and concepts necessary for the understanding of physical phenomena associated to PtG and the production of hydrogen and synthetic gas are presented.